Influence of optimal conditions of ultrasonic dispersion on the stability of suspensions of finely ground slags - Samchenko Svetlana; Kozlova Irina; Zemskova Оlga; Baskakova Ekaterina (MATEC Web of Conferences, 2019)
The preparation in the jet mill of finely ground slag (FGS) from the waste of metallurgical production granulated blast-furnace slag, the obtaining of slag suspensions, and the behavior of FGS particles in an aqueous dispersion medium are considered in the paper. It was found that FGS particles in the suspension form micelles of two types with negative (micelle 1) and positive (micelle 2) charges of FGS surface. To increase the aggregative and sedimentation stability of FGS particles in suspensions, studies were carried out using ultrasonic dispersion. The results of investigations on the detection of optimal dispersion parameters for slag suspensions are presented. It was found that in the absence of temperature control, the process of coagulation of slag particles is accelerated and aggregative and sedimentation stability of suspensions of FGS is reduced. The slag particles in the suspension form aggregates that lead to a deterioration of the strength characteristics of the cement stone using suspensions of FGS. Optimal parameters of ultrasonic dispersion of slag suspensions are established: the frequency of ultrasonic vibrations is equal to 44 kHz; the dispersion temperature is 25 ± 2 °C; the dispersion time is 15 min. It was found that the application of ultrasonic dispersion to slag suspensions with the observance of dispersion conditions can increase the aggregative and sedimentation stability of FGS suspension by 2-3 times in comparison with the mechanical mixing of suspensions. The strength of samples with suspensions of FGS prepared using UST under the recommended dispersing conditions increased by 19 to 39% in the first day; for 28 days of hardening - by 19 - 36%, which allows using slag suspensions in the production of cement composite materials and concretes based on them.